Controle de vazão de biogás com baixa pressão para produção descentralizada de eletricidade - Moreira, André Pimentel (2011)
The present dissertation proposes the implementation of a data acquisition system, control and monitoring of a electricity generation plant powered by biogas. The experimental study of the modelling strategies, identification and control was done applied to ow control of the biogas plant of the Renewable Energy Laboratory - LEA at the Federal University of Ceará - UFC. To control the biogas ow a parallel PI controller was used and tested, and the controller was used to perform the comparison with the existing control (centrifugal control) of the gen-set. To check the response of the gen-set powered by biogas, a load corresponding of 60% of the nominal power was used. The proposed system reduced the human intervention in ow setting of the expansion valve. The results showed that the stability response time after the introduction of the PI controller to the original controller allowed the reduction of the response time for at least 20% showing a satisfactory response and a stability for the transition from gasoline to biogas, with 10 Hz amplitude and 8 seconds for the system stabilization with load. This action was considered feasible to automate the process of starting up of the gen-set